1996
DOI: 10.1136/bmj.313.7051.191
|View full text |Cite
|
Sign up to set email alerts
|

Environment of infants during sleep and risk of the sudden infant death syndrome: results of 1993-5 case-control study for confidential inquiry into stillbirths and deaths in infancy

Abstract: This study confirms the importance of certain risk factors for the sudden infant death syndrome and identifies others-for example, covers over the head, side sleeping position-which may be amenable to change by educating and informing parents and health care professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
258
3
8

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(276 citation statements)
references
References 14 publications
(16 reference statements)
7
258
3
8
Order By: Relevance
“…Washington, DC 20010, Tel: 202-476-3931, Fax: 202-476-3386, lfu@cnmc As the rate of prone positioning has declined, other previously unrecognized risk factors for sudden unexplained infant death have emerged in recent epidemiologic studies. Despite the fact that bedsharing between an infant and adult facilitates breastfeeding and enhances parent-infant interactions,(6, 7) this sleeping arrangement has been identified in epidemiologic studies as being hazardous in certain situations, particularly when one or both parents are smokers,(8-12) on excessively soft surfaces, such as waterbeds, sofas, and armchairs, (9,10,(13)(14)(15) or when the infant is less than 2-3 months of age. (9,12,(14)(15)(16)(17) In addition, there is an increased risk for sudden unexpected infant death when there are multiple bedsharers(13) and when bedsharing occurs for the entire night.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Washington, DC 20010, Tel: 202-476-3931, Fax: 202-476-3386, lfu@cnmc As the rate of prone positioning has declined, other previously unrecognized risk factors for sudden unexplained infant death have emerged in recent epidemiologic studies. Despite the fact that bedsharing between an infant and adult facilitates breastfeeding and enhances parent-infant interactions,(6, 7) this sleeping arrangement has been identified in epidemiologic studies as being hazardous in certain situations, particularly when one or both parents are smokers,(8-12) on excessively soft surfaces, such as waterbeds, sofas, and armchairs, (9,10,(13)(14)(15) or when the infant is less than 2-3 months of age. (9,12,(14)(15)(16)(17) In addition, there is an increased risk for sudden unexpected infant death when there are multiple bedsharers(13) and when bedsharing occurs for the entire night.…”
mentioning
confidence: 99%
“…Multiple studies have demonstrated that bedsharing is particularly hazardous if one or both parents smoke. (10,12,16,17) A potential limitation of this study is that data collection occurred in only four cities, although demographic data indicate that infant mortality rates in Dallas, New Haven, Atlanta and Savannah of 6.3, 5.5, 7.1 and 11.0 * deaths per 1,000 live births, respectively, * Infant mortality data available at the public health district level only for Atlanta and Savannah. In conclusion, bedsharing in a low-income population is associated with African-American race and having a teenage mother.…”
mentioning
confidence: 99%
“…62 63 An example is the use of case-control methods to evaluate the impact on the incidence of sudden infant deaths of advice about sleep position and other aspects of babies' sleeping environment. [64][65][66] A crucial aspect of the design of an evaluation is the choice of outcome measures. You need to think about which outcomes are most important, and which are secondary, and how you will deal with multiple outcomes in the analysis.…”
mentioning
confidence: 99%
“…We found 11 observational studies 5, 14, 18, 24, 25, 26, 27, 28, 29, 30, 31 that consistently showed a risk reduction of about 50% if the infant used a dummy (Table 2). …”
Section: Resultsmentioning
confidence: 99%